The impact of irrigation on nutrition, health, and gender: A review paper with insights for Africa south of the Sahara - Domenech, Laia; Ringler, Claudia (International Food Policy Research Institute, 2013)
The hypothesis underlying this review paper is that how irrigation gets deployed in SSA will be decisive not only for environmental sustainability (such as deciding remaining forest cover in the region) and poverty reduction, but also for health, nutrition, and gender outcomes in the region. The focus of this paper is on the health, nutrition, and gender linkage.